Insect Plastic Degradation: A Novel Approach to Tackling the Global Plastic Crisis - Balraj, G.; Sandeep, K.; Imran, G. M.; Bonkuri, Krishna Kumar; Raju, Kamsali Pruthvi (Chronicle of Bioresource Management, 2025)
The alarming rise of plastic pollution has driven the search for innovative, sustainable solutions beyond conventional recycling and disposal. Insects have emerged as promising agents for plastic biodegradation, offering a natural, eco-friendly alternative to chemical and microbial processes. The degradation abilities of several insect species such as Galleria mellonella, Achroia grisella, Plodia interpunctella, Tenebrio molitor and Corcyra cephalonica, which have shown potential to consume and decompose polyethylene (PE), polystyrene (PS) and other synthetic polymers. The process involves mechanical breakdown via chewing, microbial action from gut flora and enzymatic depolymerization into simpler, biodegradable compounds. These insects not only tolerate plastic diets but, in some cases, complete life cycles, making them viable for long-term biowaste strategies. However, challenges like process scalability, environmental safety, and incomplete knowledge of gut microbiota mechanisms remain. Continued research into insect physiology, microbial consortia, and genetic pathways is crucial. Insect-mediated plastic degradation offers a complementary pathway towards addressing global plastic waste sustainably.